The Morality of Schooling: Women's Education as an Arena for Social Tension in Cabo Delgado - Rosario, Carmeliza (Kronos, 2024)
In this article, I reflect on education as a continuing arena of tension for people in Cabo Delgado. The tension between formal (state-sponsored) and religious education as a backdrop of the conflict in Cabo Delgado has been widely mentioned but largely misunderstood. Scholars have consistently mentioned poverty and people's lack of access to formal education as drivers of the disenfranchisement that has led to violent extremism in the province. There are also references to how the insurgent movement has shunned formal education in favour of Islamic teachings. The existing literature about the insurgent's rejection of state-sponsored education, especially for girls, fails to address a trajectory whereby formal (state-sponsored) education has been a field of tension for a long time. Similar tensions happened across the Swahili coast in both English and French colonies. From interviews focused on women's relationships and experiences with both the colonial and postcolonial state, it emerged that Muslim populations in Cabo Delgado, particularly on the coast, have a long history of suspicion towards state-sponsored education. This includes showcasing a locally established practice for women's education that predated and existed alongside formal education. This follows that cultural and religious dynamics do not preclude women's influence in society, particularly education. In fact, it relies on her active participation. At the same time, despite potential violent cooptation, in the context of the conflict, the insurgent movement is able to tap into the existing tensions, including that around state-sponsored education. Evidence from the field indicates that, despite the disadvantages of resisting formal education, religious education remains central to most people, not just those following the extremist movement. What may appear to be an extremist rupture from mainstream practice should be understood within a logic operating on shared and familiar values.